2008
DOI: 10.1159/000151582
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries Increments and Related Factors in Children with Type 1 Diabetes Mellitus

Abstract: The aim of this study was to analyse possible associations between caries increments and selected caries determinants in children with type 1 diabetes mellitus and their age- and sex-matched non-diabetic controls, over 2 years. A total of 63 (10–15 years old) diabetic and non-diabetic pairs were examined for dental caries, oral hygiene and salivary factors. Salivary flow rates, buffer effect, concentrations of mutans streptococci, lactobacilli, yeasts, total IgA and IgG, protein, albumin, amylase and glucose w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
75
0
22

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(110 citation statements)
references
References 63 publications
(55 reference statements)
10
75
0
22
Order By: Relevance
“…The latter value (Siudikiene et al, 2006) is similar to the average SSFR in well-controlled adolescents in the present study (DM1-A group, 1.140 mL/min, Table 2). The average SSFR value was significantly different between DM1 group (0.932 mL/min) and control group (1.224 mL/min), which is in consonance with previous studies with adolescents with DM1 (Siudikiene et al, 2006(Siudikiene et al, , 2008. In the present study, hyperglycemia was associated to a reduction in salivary flow (Table 2).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The latter value (Siudikiene et al, 2006) is similar to the average SSFR in well-controlled adolescents in the present study (DM1-A group, 1.140 mL/min, Table 2). The average SSFR value was significantly different between DM1 group (0.932 mL/min) and control group (1.224 mL/min), which is in consonance with previous studies with adolescents with DM1 (Siudikiene et al, 2006(Siudikiene et al, , 2008. In the present study, hyperglycemia was associated to a reduction in salivary flow (Table 2).…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, xerostomia was shown to have a negative impact on the quality of life of adolescents with DM1 (Busato et al, 2009). The relationship among DM1, salivary composition and xerostomia has been widely investigated (Swanljung et al, 1992;Moore et al, 2001;López et al, 2003;Siudikiene et al, 2006;Siudikiene et al, 2008;Orbak et al, 2008). It has been found that most DM1 patients have salivary dysfunction as well as differences in biochemical salivary composition compared with healthy subjects (Swanljung et al, 1992;Moore et al, 2001;López et al, 2003;Siudikiene et al, 2006;Siudikiene et al, 2008;Orbak et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Si bien no se observó una asociación estadística entre el tipo de dieta y la presencia de caries, los resultados no son concluyentes y pueden deberse a la baja proporción de pacientes DM1 con dieta cariogénica tipo moderada. Sin embargo, el riesgo de caries en pacientes diabéti-cos se asocia principalmente a los cambios en la composición y flujo de la saliva (aumento en las concentraciones de glucosa y albumina), un pobre control de la placa bacteriana 26,27 y un mal control metabólico de la diabetes 28 tal como se presenta en la población seleccionada en este reporte.…”
Section: Discussionunclassified
“…La forte prévalence de la carie chez les diabétiques peut aussi s'expliquer par un taux de glucose plus élevé dans leur salive [2]. Nos résultats corroborent ceux de Siudikiene et al [21,23,24]. Les enfants Tableau VI.…”
Section: Discussionunclassified